Performance Testing of Power Breaker 20 kV at the Senayan PLTMG Substation Netto Cubicles - Sri Hartanto; Tri Ongko Priyono; Reza Pahlavi; Dubois Benoît (Scientechno: Journal of Science and Technology, 2023)
A Power Breaker is a mechanical switch that is able to open to allow current to flow under normal conditions and close when there is a disturbance under abnormal conditions, such as a short circuit current disturbance. Damage to the Power Breaker has a considerable influence on the operation of the electric power system, resulting in losses and the operating system of the electric power being disrupted. For this reason, it is necessary to periodically test Power Breaker performance in order to meet operating standards, improve reliability, guarantee quality, and maintain the continuity of electric power distribution. This research was limited to testing before and after the Power Breaker 20 kV Net Cubicles Maintenance located at the Senayan PLTMG Substation during February 2023 in the form of contact resistance testing, Insulation resistance testing, simultaneity testing, and trip relay testing. By testing the performance of the Power Breaker, it is hoped that it can prevent malfunctions that result in damage to the Power Breaker and other components at the Senayan PLTMG Substation